STRATEGI PEMBELAJARAN MURDER UNTUK MENINGKATKAN PEMAHAMAN SISWA SMA: Penelitian Tindakan di SMA 1 Unggulan BPPT Darul Ulum Jombang - Emi Lilawati; Hidayatur Rohmah (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2019)
The background of the problem of this research is that the teacher in conducting learning has not fully implemented an appropriate learning model and is in accordance with the way students learn. This raises a problem when teachers apply a monotonous learning model and there is no compatibility with the learning styles of their students, the learning process does not attract students' learning interest so students have difficulty understanding the material being taught. The problem in this study is: how is the effectiveness of the MURDER learning strategy (Mood, Understand, Recall, Digest, Expand, Review) to improve the understanding ability of high school students, whether the MURDER learning strategy (Mood, Understand, Recall, Digest, Expand, Review) can improve the comprehension ability of high school students. This research is a Classroom Action Research (CAR). In the learning process researchers use Fiqh subjects as research material. The subjects of the study were students of Class X IPA 1 High School BPPT Darul Ulum Jombang. Data collection is done by observation, interviews, and tests to complete the data revealed. Meanwhile, to obtain the validity of the data, the authors use technical triangulation analysis. Source triangulation is used to test the credibility of the data carried out by checking the data obtained through several sources.